Specific Instruments to Assess Quality of Life in Children and Adolescents with Asthma - Cristian Roncada; Rita Mattiello; Paulo M. Pitrez; Edgar E. Sarria (Brazilian Society of Pediatrics, 2013)
Objective: To identify and describe specific instruments to assess health-related quality of life (HRQoL) in children and adolescents with asthma. Data source: : Searches were performed in the PubMed, Ovid, and LILACS databases using different combinations of key words (MeSH terms), selecting original articles on the development of specific HRQoL questionnaires, published in English, Portuguese, or Spanish, between 1990 and 2012. Data synthesis: : A total of 15 instruments that met the inclusion criteria were identified. Most studies assessed reliability through internal consistency, reproducibility, and/ or sensitivity to changes. Validity was assessed by comparison with healthy controls (discordant validity) or factorial analysis. Conclusions: Of the 15 instruments, three are the most frequently used: Pediatric Asthma Quality of Life Questionnaire (PAQLQ), Pediatric Quality of Life Inventory 4.0 (PedsQL- Asthma), and Disability Kids (DISABKIDS). In general, these three tools have adequate psychometric characteristics and are practical to implement, but only PAQLQ has been culturally adapted to Brazil.